Mecanismos de combate á corrupção e a experiência do governo do estado do Maranhão de 2015 A 2017 - Emilio, Marcos Roberto (2018)
This Master Thesis aims to study the main mechanisms for preventing and fighting corruption, emphasizing those of transparency and accountability; in addition to understand how these public policies are built, it seeks to understand the importance of State and society in running these mechanisms and to analyze the experience of the State Government of Maranhão related to the fight against corruption between 2015 and 2017. In order to understand the phenomenon of corruption, firstly it is necessary to understand the particularities of its conceptualization, classification and measurement, once it is necessary to consider the context of its occurrence, laws in force and its effects in society. Therefore, a research was also carried out on the concept of corruption through a brief analysis of the modern period using Machiavelli's thought and main trends in social sciences in the contemporary period, seeking to achieve its expression in the Brazilian reality